Happiness, Gratitude, Life Satisfaction, and Life Orientation among Working and Non-working Individuals - Mussarat Jabeen Khan; Umey Kalsoom; Iqra Shahzadi Shahzadi; Faiza Abbasi; Naseem Akhtar (NUST Journal of Social Sciences and Humanities, 2022)
The study was conducted to find differences among working and non-working individuals regarding happiness, gratitude, life satisfaction, and life orientation. Convenient sampling technique was used to collect the data. The sample consisted of 300 individuals; 150 were working and 150 were non-working individuals. Out of 150 working participants, 75 participants were bankers and 75 were teachers. The non-working sample consisted of 75 males and 75 females. Oxford Happiness Questionnaire, The Gratitude Questionnaire-six item form (GQ- 6), Satisfaction with Life Scale and Life Orientation Test-Revised were used to measure happiness, gratitude, life satisfaction, and life orientation respectively. Correlation unveiled that happiness, gratitude, life satisfaction, and life orientation were positively correlated. Independent sample t-test showed that working individuals were happier, more grateful, and more satisfied with life as compared to non-working individuals while non-working females showed higher levels of gratitude, satisfaction, and positive life orientation than non-working men. Further independent sample t test indicated that bankers were happier than teachers. Multiple regression analysis showed that happiness and gratitude predict life satisfaction.